2018
DOI: 10.1016/j.scib.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Protonation induced high- T c phases in iron-based superconductors evidenced by NMR and magnetization measurements

Abstract: Chemical substitution during growth is a well-established method to manipulate electronic states of quantum materials, and leads to rich spectra of phase diagrams in cuprate and iron-based superconductors. Here we report a novel and generic strategy to achieve nonvolatile electron doping in series of (i.e. 11 and 122 structures) Fe-based superconductors by ionic liquid gating induced protonation at room temperature. Accumulation of protons in bulk compounds induces superconductivity in the parent compounds, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 42 publications
3
35
0
1
Order By: Relevance
“…We attribute it to the easier formation of A 2 Se (A is the akaline metals) impurity for Na and K with the increase of reactivity. Recently, the hydrogen intercalated FeSe 0.93 S 0.07 single crystal is also reported to have an improved T c although the intercalation is not uniform [29]. The above results inspire us to intercalate new intercalator that is chemically inert in the sequence table of metal activity.…”
Section: Introductionmentioning
confidence: 96%
“…We attribute it to the easier formation of A 2 Se (A is the akaline metals) impurity for Na and K with the increase of reactivity. Recently, the hydrogen intercalated FeSe 0.93 S 0.07 single crystal is also reported to have an improved T c although the intercalation is not uniform [29]. The above results inspire us to intercalate new intercalator that is chemically inert in the sequence table of metal activity.…”
Section: Introductionmentioning
confidence: 96%
“…This is in sharp contrast to conventional electric double layer transistor (EDLT) using ionic liquids 16,17 , where charge carrier concentration is tuned through interfacial electrostatic effect while electrochemical reaction is intentionally avoided. It is interesting to note that recent studies reveal that the electrolysis of water residual within the ionic liquid could also lead to intercalation of oxygen and hydrogen ions 18 , which however has negligible effect on the interlayer spacing 19 . In strong contrast, here we achieve successful intercalation of large organic cation (for example, [C 2 MIm] + with chemical formula of [C 6 H 11 N] + 2 ) into these layered crystals with dramatically increased interlayer spacing.…”
mentioning
confidence: 99%
“…Recently, Shi et al reported that under a large bias and using a KClO 4 /polyethylene glycol electrolyte, a electrochemical reaction between the electrolyte and channel material can occur, resulting in bulk ionic doping and an accumulation of carriers far beyond the level of electrostatic surface doping, leading to the observation of superconductivity in MoTe 2 [135]. Cui et al further utilized protonation process to induce the high T c phase in iron-based superconductors [26]. The proton doping process and setup are illustrated in Figure 16 (a) [26].…”
Section: Spintronic and Superconducting Devicesmentioning
confidence: 99%
“…In the layered transition metal dichalcogenide TiS 2 , the thermoelectric figure of merit can be enhanced by at least a factor of four through ion intercalation [25]. Furthermore, recent studies have shown that the transition temperature of iron-based superconductors can be elevated by reversible ion doping, with results similar to those from substitutional alloy doping [26]. These experimental observations demonstrate that ion intercalation is capable of manipulating band structure and the properties of materials beyond traditionally explored paradigms such as strain engineering, alloying, electrostatic gating, and electromagnetic field excitation.…”
mentioning
confidence: 97%
See 1 more Smart Citation